2019
DOI: 10.1093/molbev/msz068
|View full text |Cite
|
Sign up to set email alerts
|

Complete Inactivation of Sebum-Producing Genes Parallels the Loss of Sebaceous Glands in Cetacea

Abstract: Genomes are dynamic biological units, with processes of gene duplication and loss triggering evolutionary novelty. The mammalian skin provides a remarkable case study on the occurrence of adaptive morphological innovations. Skin sebaceous glands (SGs), for instance, emerged in the ancestor of mammals serving pivotal roles, such as lubrication, waterproofing, immunity, and thermoregulation, through the secretion of sebum, a complex mixture of various neutral lipids such as triacylglycerol, free fatty acids, wax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 65 publications
5
37
0
Order By: Relevance
“…Although certain glands are conserved across large, ancient taxonomic groupsmammary glands and insect oenocytes being examples (Blomquist and Bagneres, 2010;Chung and Carroll, 2015;Makki et al, 2014;Oftedal, 2002) such examples are few, and are dwarfed by the myriad unique exocrine glands common only to specific taxa of lower rank (Blum, 1996; http:// www.pherobase.com). Moreover, even highly conserved glands can be subject to repeated loss, as evidenced by the absence of mammalian sebaceous glands in cetaceans, hippos, elephants and naked mole rats (Lopes-Marques et al, 2019).…”
Section: Box 1 a Snapshot Of Animal Gland Diversitymentioning
confidence: 99%
“…Although certain glands are conserved across large, ancient taxonomic groupsmammary glands and insect oenocytes being examples (Blomquist and Bagneres, 2010;Chung and Carroll, 2015;Makki et al, 2014;Oftedal, 2002) such examples are few, and are dwarfed by the myriad unique exocrine glands common only to specific taxa of lower rank (Blum, 1996; http:// www.pherobase.com). Moreover, even highly conserved glands can be subject to repeated loss, as evidenced by the absence of mammalian sebaceous glands in cetaceans, hippos, elephants and naked mole rats (Lopes-Marques et al, 2019).…”
Section: Box 1 a Snapshot Of Animal Gland Diversitymentioning
confidence: 99%
“…Reductive episodes have been widely documented across the tree of life contributing to organismal divergence and physiological and morphological adaptation to environmental cues (Albalat & Cañestro, 2016; Braun, 2003; Jeffery, 2009; Olson, 1999). In agreement, gene loss mechanisms seem pervasive in lineages that endured drastic habitat transitions in the course of evolution, such as Cetacea, entailing niche-specific adaptations (Huelsmann et al, 2019; Lachner et al, 2017; Lopes-Marques et al, 2018; Lopes-Marques et al, 2019a; McGowen, Gatesy & Wildman, 2014; Nery, Arroyo & Opazo, 2014; Sharma et al, 2018; Strasser et al, 2015). Thus, our findings suggest that these species are natural KOs for this dopamine receptor and might offer valuable insights into the mechanisms of some forms of essential hypertension.…”
Section: Introductionmentioning
confidence: 72%
“…This is particularly relevant in the context of gene loss and the unique phenotype adaptations of Cetacea. Recently, a surge of studies has specifically demonstrated the relevance of disabling mutations in the coding region of genes as a source of adaptive success in land to water habitat transitions (e.g., Meyer et al, 2018;Huelsmann et al, 2019;Lopes-Marques et al, 2019b). This evolutionary trend of gene reduction has been particularly prevalent in the gene families involved in skin physiology (Figure 1), with a minimum of 36 described events of gene inactivation, and strongly correlate with specific Cetacea phenotypic traits (e.g., keratins and absence of pelage).…”
Section: Future Perspectives: Cetacea Genomes and The Role Of Gene Lossmentioning
confidence: 99%